Performance of the dentist in assisting adolescents in Brazil (Research, Society and Development, 2021)
To identify the scientific production about research on adolescent care in Brazilian dentistry. Virtual searches were conducted in the PubMed, BIREME, Web of Sciences, LILACS and BBO databases from September 2020. It was observed that 34.8% of the published articles were concentrated in the Northeast and Southeast regions. In relation to the thematic axes addressed by the present investigations it can be noticed that, 43.5% of the articles highlighted the need for access to oral health services. 17.4% highlighted the prevalence and needs of oral health care and 17.4% associated the diagnosis and incidence of comorbidities. Therefore, it is necessary that multicenter research centers and the family health strategy adopt preventive and health promotion measures considering the socioeconomic indicators of each region, thus promoting the link between the dental surgeon and the adolescent patient.